2023
DOI: 10.1021/acs.orglett.3c01448
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Formation of α-Amino Acid Derivatives via [2,3]-Sigmatropic Rearrangement of N-Acyl Iminosulfinamides

Abstract: An aza-variation on [2,3]-sigmatropic rearrangement of allylic sulfimides was developed. In this process, enolization of N-acyl iminosulfinamides was followed by O-silylation to generate O-silyl Niminosulfinyl N,O-ketene aminal intermediates, which undergo a [2,3]shift to afford α-sulfenylamino imidates that were converted to the corresponding carboxamides after desilylation triggered by acidic aqueous workup. Chirality is transferred from the sulfur stereocenter to the α-carbon, thereby enabling the enantiose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 76 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…A proposed catalytic cycle is depicted in Figure . , The ynamide reacted with HNTf 2 to form a keteniminium species, which was subsequently captured by sulfinamide through O -addition. The kinetically favored ( E )-enolonium intermediate underwent rapid [2,3]-rearrangement to give an α-amino acid skeleton, thereby releasing a proton as catalyst for further catalytic cycle.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A proposed catalytic cycle is depicted in Figure . , The ynamide reacted with HNTf 2 to form a keteniminium species, which was subsequently captured by sulfinamide through O -addition. The kinetically favored ( E )-enolonium intermediate underwent rapid [2,3]-rearrangement to give an α-amino acid skeleton, thereby releasing a proton as catalyst for further catalytic cycle.…”
mentioning
confidence: 99%
“…In a complementary approach by the same group, treatment of chiral sulfinamides with similar reaction intermediates generated in situ from amide activation yielded the UAA derivatives with an inverted configuration and improved enantioselectivity . An intramolecular rearrangement reaction of chiral iminosulfinamides recently also resulted in similar products …”
mentioning
confidence: 99%
“…In this study, we have successfully demonstrated the viability of the anticipated transformations, leading to the enantioselective synthesis of α-tertiary amino amides (Scheme B, i) or 5,5-disubstituted 3,5-dihydro-4 H -imidazol-4-ones (Scheme B, ii), depending upon the specific N 2 substituents present in sulfinamidines. Notably, this work represents a rare example of the asymmetric formal 1,2-diamination of disubstituted ketenes through a nitrogen analogue of aza-Mislow–Evans rearrangement …”
mentioning
confidence: 99%
“…The sulfinamidine product 2 then underwent N 1 -tosylation and N 2 -deprotection, leading to the production of tosyl sulfinamidine 3a with high enantiopurity [>99% enantiomeric excess (ee)]. The absolute configuration of compound 3a was determined to be ( R S ) through comparison of its optical rotation with that of a previously prepared authentic sample . Noteworthy is the enhanced convenience of the new method compared to the initial protocol involving enantiomeric resolution .…”
mentioning
confidence: 99%
“…Organic and medicinal chemists have been persistently endeavoring to establish efficacious asymmetric catalytic methodologies for the synthesis of these compounds. Recently, some efforts have focused on devising syntheses of chiral α-amino carbonyl compounds, including electrophilic amination of ketones, amination of α-halogenated carbonyls, asymmetric hydrogenation of ketimines, insertion reaction of diazo compounds and sulfonium ylides, α-iminol rearrangement, cross-dehydrogenative amination, and others . However, the application of these methods was constrained by limited stereoselectivities, prefunctionalization of substrates or reliance on special functional substrates such as 1,2-dicarbonyl compounds and α-hydroxyketones, etc., utilization of toxic excess metals, and multistep synthesis.…”
mentioning
confidence: 99%